2002
DOI: 10.1103/physrevb.66.214205
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic photonic band gap and anisotropic structures in transmission spectra of two-dimensional fivefold and eightfold symmetric quasiperiodic photonic crystals

Abstract: We measured and calculated transmission spectra of two-dimensional quasiperiodic photonic crystals (PCs) based on a 5-fold (Penrose) or 8-fold (octagonal) symmetric quasiperiodic pattern. The photonic crystal consisted of dielectric cylindrical rods in air placed normal to the basal plane on vertices of tiles composing the quasiperiodic pattern. An isotropic photonic band gap (PBG) appeared in the TM mode, where electric fields were parallel to the rods, even when the real part of a dielectric constant of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Such quasiperiodic optical lattices can be created in the 2D case, as a combination of N = 4, N = 5 (Penrose tiling-a pattern of tiles, which completely cover an infinite plane in an aperiodic manner) or N 7 quasi-1D sublattices with wave vectors k (n) . The band-gap spectrum of 2D photonic crystals of the PT type has been studied in [43][44][45]. Recently the interesting properties of such lattices (e.g., Penrose lattices), have been discovered for quasiperiodic pinning arrays [46].…”
Section: Basic Equationsmentioning
confidence: 99%
“…Such quasiperiodic optical lattices can be created in the 2D case, as a combination of N = 4, N = 5 (Penrose tiling-a pattern of tiles, which completely cover an infinite plane in an aperiodic manner) or N 7 quasi-1D sublattices with wave vectors k (n) . The band-gap spectrum of 2D photonic crystals of the PT type has been studied in [43][44][45]. Recently the interesting properties of such lattices (e.g., Penrose lattices), have been discovered for quasiperiodic pinning arrays [46].…”
Section: Basic Equationsmentioning
confidence: 99%
“…They investigated the dependence of the transmittance on the extension of the crystal sample and found that the spectral gaps can be found in rather small subsections of a structure. Their conclusion was that local scattering is governing the formation of bandgaps rather than global scattering and that therefore long-range periodic order is not a prerequisite for the existence of a gap (see also Hase et al [8]). Wang et al [9] then discovered, that there are sharp peaks in transmittance spectra of defect-free photonic quasicrystals, which are associated with modes strictly localized at singularities in the structure.…”
Section: Introductionmentioning
confidence: 96%
“…Such geometries, intrinsically tied with the concept of "quasicrystals" in solid-state physics [4], are gaining a growing attention in many branches of science and technology [5]. In electromagnetics engineering, recent studies on EBG quasicrystals [7]- [13] have confirmed the possibility of obtaining effects and properties similar as those exhibited by periodic EBG structures, with potential advantages (e.g., larger bandgaps, lower and/or multiple frequencies of operation, higher isotropy, richer and more wavelength-selective defect states, easier achievement of phase-matching conditions) via a judicious exploitation of the additional degrees of freedom typically available in aperiodic structures. Interesting applications have been proposed to lasers [14], negative refraction and superlensing [15], nonlinear optical frequency conversion [16], wavelength-division multiplexing [17], enhanced transmission through subwavelength hole arrays [18], directive emission [19], etc.…”
Section: Introduction and Back-groundmentioning
confidence: 99%